The Therapeutic Effects of Medicinal Plants on Depression and Anxiety Disorders - Seyed Ebrahim Hosseini; Seyed Ali Hosseini (Islamic Azad University, 2018)
Anxiety and depression are among the commonly occurring illnesses around the world that cause changes in the lifestyle of humans and impose huge costs to treat these disorders on human societies. These disorders can be associated with physiological symptoms such as tachycardia, sweating, respiratory dysfunction, numbness, and sometimes paralysis of the limbs, etc. In the treatment of these diseases, the goal is to help people to minimize the risk of following side effects while healing these disorders. In the treatment of drugs in the past, benzodiazepine drugs such as diazepam (valium), alprazolam (xanax), lorazepam (ativan), and baspiron were used to treat anxiety disorders. However, presently anti-depressant drugs such as fluxetin, paroxetine, sertaline, and venlafaxine are more widely administered. It is estimated that between 10 to 20% of people in the western hemisphere use these drugs almost regularly . In depression studies, monoamine neurotransmitters such as serotonin (5- HT), neuroadrenaline (NA) and dopamine (DA) play an important role in mediating depressive behaviors. Various studies have shown that major depressive symptoms are caused by a reduction in the function of these neurotransmitters. Monoamine oxidase enzyme (MAOA) is also a key enzyme dependent on the metabolism of neurotransmitters, and it has been suggested that its activity is one of the indicators of psychosomatic susceptibility. It has also been observed that the hypothalamic-pituitary-adrenal axis (HPA) is impaired in patients with depression. The use of herbal medicine has been commonplace in ancient civilizations, and hence since ancient times plants have long been an important source of medicine. Research on plants in recent years has shown that plants such as chamomile and lavender, which have formerly been used to treat anxiety and depression have anti-anxiety and anti-depression effects; accordingly, in the present study, the effects of 18 plant types on the treatment of these disorders have been investigated.